A pharmacokinetic‐pharmacodynamic study of a single dose of febuxostat in healthy subjects. Issue 12 (18th June 2020) - Kamel, Bishoy; Graham, Garry G.; Stocker, Sophie L.; Liu, Zhixin; Williams, Kenneth M.; Carland, Jane E.; Pile, Kevin D.; Day, Richard O.
Abstract : Aims: To examine the pharmacokinetic‐phamacodynamic (PK‐PD) relationships of plasma febuxostat and serum urate and the effect of a single dose of the drug on renal excretion and fractional clearance of urate (FCU). Methods: Blood and urine samples were collected at baseline and up to 145 hours following administration of febuxostat (80 mg) to healthy subjects (n = 9). Plasma febuxostat and serum and urinary urate and creatinine concentrations were determined. Febuxostat pharmacokinetics were estimated using a two‐compartment model with first‐order absorption. An Emax PK‐PD model was fitted to mean febuxostat and urate concentrations. Urinary urate excretion and FCU were calculated pre‐ and post‐dose. Results: Maximum mean plasma concentration of febuxostat (2.7 mg L −1 ) was observed 1.2 hours after dosage. Febuxostat initial and terminal half‐lives were 2.0 ± 1.0 and 14.0 ± 4.7 hours (mean ± SD), respectively. The majority (81%) of the drug was eliminated in the 9 hours after dosing. Serum urate declined slowly achieving mean nadir (0.20 mmol L −1 ) at 24 hours. The IC50 (plasma febuxostat concentration that inhibits urate production by 50%) was 0.11 ± 0.09 mg L −1 (mean ± SD). Urinary urate excretion changed in parallel with serum urate. There was no systematic or significant change in FCU from baseline. Conclusion: The PK‐PD model could potentially be used to individualise febuxostat treatment and improve clinical outcomes. A single dose of febuxostat does not affect the efficiency of the kidney to excrete urate. Further investigations are required to confirm the present results following multiple dosing with febuxostat.